2010
DOI: 10.1068/p6401
|View full text |Cite
|
Sign up to set email alerts
|

Now You Feel it, Now You Don't: How Robust is the Phenomenon of Illusory Tactile Experience?

Abstract: Recent studies have reported that in normal healthy individuals, the perception of illusory sensations in one modality can be induced by the presentation of a stimulus in another modality. These illusory sensations may arise from the activation of a tactile representation in memory induced by the non-target stimulus, in a process mirroring that thought to be responsible for many forms of medically unexplained symptoms. The reliability of illusory-touch reports was investigated here in two experiments with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 38 publications
(39 reference statements)
9
32
0
Order By: Relevance
“…Inclusion of the simultaneous task irrelevant light was also found to significantly increase vibration reports regardless of whether or not one was present; leading to increases in both hit rates and false-alarm rates. This result replicates previous findings (Johnson, Burton & Ro, 2006;Lloyd et al, 2008;McKenzie, Poliakoff, Brown et al, 2010;Mirams et al, 2010) and suggests that if visual information is available, participants incorporate it into decisions about ambiguous somatic events, even when such visual information is entirely task-irrelevant.…”
Section: Discussionsupporting
confidence: 89%
“…Inclusion of the simultaneous task irrelevant light was also found to significantly increase vibration reports regardless of whether or not one was present; leading to increases in both hit rates and false-alarm rates. This result replicates previous findings (Johnson, Burton & Ro, 2006;Lloyd et al, 2008;McKenzie, Poliakoff, Brown et al, 2010;Mirams et al, 2010) and suggests that if visual information is available, participants incorporate it into decisions about ambiguous somatic events, even when such visual information is entirely task-irrelevant.…”
Section: Discussionsupporting
confidence: 89%
“…The use of visual stimuli is not directly related to MUS, but it serves as an example in order to create a laboratory model of MUS. This process is understood as a phenomenon of normal multisensory integration, not as a consequence of conditioning [10]. Mirams, Poliakoff, Brown, and Lloyd [11] found that attending to the body had an effect on the number of false alarms (FAs) (i.e., illusory touch experiences) in the SSDT paradigm.…”
Section: The Somatic Signal Detection Paradigmmentioning
confidence: 99%
“…Vice versa, illusory tactile sensations and an enhancement of tactile sensitivity can be triggered by visual stimuli [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The light stimulus is expected to trigger illusory touch perceptions by activating representations of the tactile stimulus in the light-only condition (Lloyd et al, 2008). Within the paradigm, this effect is attributed to normal multisensory integration, rather than potential conditioning processes between the light and tactile stimulus (McKenzie, Poliakoff, Brown, & Lloyd, 2010). Attending to the body also has an effect on false-alarm rates: for example, illusory touch experiences are significantly more likely in light-present trials when participants have the opportunity to look at their hand (Mirams, Poliakoff, Brown, & Lloyd, 2010).…”
Section: The Somatic Signal Detection Paradigmmentioning
confidence: 99%